Адаптивный потенциал культурных растений: (эколого-генетические основы) / А. А. Жученко - Жученко Александр Александрович (Штиинца, 1988)
Экземпляры: КХ (20060505) / Инвентарный номер: 919505 / Сис.шифр: 41.3 / Авт.знак: Ж 94 / ГРНТИ: 68 / ББК: 41.31